The tale of two great crises - Michele Fratianni; Federico Giri (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2015)
The great depression of 1929 and the great financial crisis of 2008 have been the two big events of the last 75 years. Not only have they produced serious economic consequences but they also changed our view of economics and policymaking. The aim of this work is to compare these two great crises and highlight similarities as well as differences. Monetary policy, the exchange rate system and the role of the banks are our fields of investigation. Our findings are that two big events have more similarities than dissimilarities.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: E5; E31; E42; G21; 330; Great Depression; Great Financial Crisis; gold standard; Eurozone; money multiplier; shadow banking